An investigation into the use of metaphor and simile expressing the concept of wealth in "The great Gatsby" by Francis Scott Key Fitzgerald - Võ, Hoàng Tâm Nguyên. (The University of Da Nang, 2014)
For a long time, English literature has always been an interesting but challenging subject to Vietnamese learners of English. One of the major causes is that the learners are not fully awake to the effective assistance of stylistics in literary analysis. The aim of the present research is to examine metaphors and similes expressing the concept of wealth in the novel “The Great Gatsby” by Francis Scott Fitzgerald. The novel is one of the most outstanding works of the famous American writer, where Fitzgerald gives the reader an idea of American Dream, and also persuades us that money cannot buy happiness. As we can see, the concept of wealth is presented throughout the entire novel. And to make it more expressive, Fitzgerald has applied to numerous expressive means and stylistic devices, where metaphor and simile play leading roles. This paper may be defined as stylistic analysis, as we treat with the style of the writer, the stylistic means and devices he used. And such an analysis is an attempt to find the artistic principles underlying the writer’s choice of language. Before focusing on Metaphor and Simile used in the novel, I have analysed all the stylistic devices used in the novel. To get a clear picture of Metaphor and Simile expressing the meaning of wealth in the novel, I have found out and analyzed more than 40 examples of Metaphors and Similes expressing the concept of wealth in the novel. This has led us to interest remarks on the two devices and their contributions on the success of the work. Basing on the findings and results of the study, the researcher suggests some implications for the teaching and learning of English literature